Scientific support of small fruit growing in Russia and prospects for its development - I. M. Kulikov; S. M. Evdokimenko; T. A. Tumaeva; A. V. Kelina; F. F. Sazonov; N. V. Andronova; M. A. Podgaetsky (Вавиловский журнал генетики и селекции)
It is possible to achieve the target indices of the Russian Doctrine of Food Security (self-sufficiency in fruits and berries should be at least 60 %) by combining the competencies of science and business. At present, hundreds of varieties of small fruit crops are included in the State Register of Breeding Achievements Admitted for Use. Domestic breeders have obtained substantial results; the share of their assortment is 79–100 %. Federal Research Center of Horticulture (Moscow) (101 pcs.), Federal Altai Research Center of Agrobiotechnology (Barnaul) (85 pcs.), Michurin Federal Research Center (Michurinsk) (42 pcs.) are the leaders in the number of created hybrids and varieties. Over the past five years, 133 new breeding achievements of traditional small fruit crops have been submitted to the State variety testing, the originators of which are research institutions, private companies and individuals. The creation of modern seed-breeding (nursery-breeding) centers (SBC) on the basis of leading specialized research institutions is expected to be the solution to the problems of modern breeding and nursery breeding and to give impetus to the development of domestic small fruit growing. The research programs of the SBC involve an integrated approach that combines the knowledge and capabilities of researchers from different disciplines, the concentration of a complex analytical instrument base in the Centers of collective use, the using of biotechnological and molecular genetic research, along with traditional methods of breeding. An analysis of the achievements in small fruit growing in research institutions under the jurisdiction of the Ministry of Science and Higher Education of the Russian Federation revealed a huge scientific potential (genetic collections, hybrid funds) for creating competitive commercial varieties and technologies for their cultivation by establishing plantations with certified planting material in accordance with international requirements. Information from literary sources indicates that one of the main criteria for the value of varieties is resistance to harmful viral diseases. The cultivation of such varieties will reduce the cost of producing planting material for small fruit crops of the highest quality categories. In the near future, the most relevant areas for the breeding of small fruit crops will be: breeding for resistance to the most harmful viruses, winter hardiness, increased transportability and long-term post-harvest storage of fruits, suitability for mechanized cultivation, high content of biologically active substances.